2010
DOI: 10.1128/jvi.01879-09
|View full text |Cite
|
Sign up to set email alerts
|

New, Closely Related Haloarchaeal Viral Elements with Different Nucleic Acid Types

Abstract: Metagenomic studies have increased the amount of information on the nucleotide sequence space in our environment. It has also increased our awareness of the viral abundance and diversity not recognized before (16,24,26). Along with this new information, we have learned to acknowledge the significance of viruses in the evolution and behavior of other organisms (55

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
132
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(135 citation statements)
references
References 64 publications
3
132
0
Order By: Relevance
“…Comparative analyses revealed that it is remarkably similar to the dsDNA genome of HHPV-1 in both gene content and organization (Fig. 8), leaving no doubt about the evolutionary relationship between these ssDNA and dsDNA viruses (204,236). In addition, the patterns of virion structural proteins were also very similar for HHPV-1 and HRPV-1 (236).…”
Section: Euryarchaeal Virusesmentioning
confidence: 76%
See 4 more Smart Citations
“…Comparative analyses revealed that it is remarkably similar to the dsDNA genome of HHPV-1 in both gene content and organization (Fig. 8), leaving no doubt about the evolutionary relationship between these ssDNA and dsDNA viruses (204,236). In addition, the patterns of virion structural proteins were also very similar for HHPV-1 and HRPV-1 (236).…”
Section: Euryarchaeal Virusesmentioning
confidence: 76%
“…Such a module is not present in the circular HHPV-1 genome, which instead encodes a putative rolling-circle replication (RCR) initiation protein at an equivalent Fig. 8) (204,236). It therefore seems that His2 or HHPV-1 donated a block of structural protein-coding genes to a linear plasmid and a circular plasmid, respectively, thereby transforming a plasmid into a virus.…”
Section: Euryarchaeal Virusesmentioning
confidence: 99%
See 3 more Smart Citations